The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.chemmater.0c04832
|View full text |Cite
|
Sign up to set email alerts
|

Interzeolite Conversion and the Role of Aluminum: Toward Generic Principles of Acid Site Genesis and Distributions in ZSM-5 and SSZ-13

Abstract: The performance of zeolite catalysts depends not only on the strength and number of Brønsted acid (or exchange) sites but also on synergistic effects derived from their proximity, in particular, and their distribution, in general. Little is known on the genesis of acid sites and site distributions in hydrothermal zeolite synthesis. By an extensive study of five crystallization systems yielding ZSM-5 (MFI) and SSZ-13 (CHA), with a focus on interzeolite conversion (IZC) methods, several synthesis factors and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 108 publications
3
53
0
Order By: Relevance
“…127 A good argument in favour of non-selective heterogeneous nucleation can be found from our kinetic study of FAU-to-MFI and FAU-to-CHA (Si/Al P ¼ 40). 47 In this work, it was demonstrated that nucleation occurred swily around one hour of FAU-to-MFI vs. 16 hours for amorphous (non-IZC) counterparts. The same time is required for FAU-to-CHA in equimolar compositions, which is a more structuralsimilar transformation.…”
Section: Role Of Al In Nucleationmentioning
confidence: 73%
See 4 more Smart Citations
“…127 A good argument in favour of non-selective heterogeneous nucleation can be found from our kinetic study of FAU-to-MFI and FAU-to-CHA (Si/Al P ¼ 40). 47 In this work, it was demonstrated that nucleation occurred swily around one hour of FAU-to-MFI vs. 16 hours for amorphous (non-IZC) counterparts. The same time is required for FAU-to-CHA in equimolar compositions, which is a more structuralsimilar transformation.…”
Section: Role Of Al In Nucleationmentioning
confidence: 73%
“…Some interesting studies are those reporting (changes in) element yields throughout the crystallization process. 47,65,93,107 Nishitoba et al present exemplary temporal results in their LTLto-CHA and FAU-to-CHA IZC (Si/Al P ¼ 3.0; Si/Al B ¼ 15, Fig. 6).…”
Section: Role Of Al During Growthmentioning
confidence: 95%
See 3 more Smart Citations